Hungarian Monitoring, 20 May 1990 . [Magyar rádiófigyelő], 1990. május 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Disarmament world conference - Shevardnadze-Baker talks Domestic Affairs: - Árpád Göncz returns from the USA - Meeting of Foreign Ministers in Vienna - Delegation of the Hungarian Parliament in Bonn - László Tőkés about the Romanian elections Külpolitika: - Leszerelési világkonferencia - Sevarnadze-Baker találkozó Belpolitika: - Göncz Árpád hazaérkezett az Egyesült Államokból - Külügyminiszteri találkozó Bécsben - Magyar parlamenti küldöttség Bonnban - Tőkés László a romániai választásokról